How to improve the students’ pre How to improve the students’ presentation skill. : How to improve the students’ presentation skill. - Majidova, Gulruh (Maktabgacha taʼlim jurnali, 2022)
Abstract: The article discusses the problems that arise while making presentation and speaking in public that many students encounter in their practice. As speaking in front of a group of people with presentation is an inevitable part of students’ assignments in their study or project work they have to develop their presentation skill. Throughout the article some tips are offered for the students to apply which will hopefully be helpful in their practice.